Relevansi Filsafat Dalam Pembentukan Paradigma Pendidikan Modern - Legi, Hendrik; Legi, Devarsh Gevariel Dean (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Through the study of philosophy, education not only functions as a means of transferring knowledge, but also as a vehicle for character building, critical thinking, and social awareness of students. This research uses a qualitative approach with a library research method, which aims to analyze the implications of philosophy for modern education. Data were obtained from various sources of academic literature, including books, scientific journals, and education policy documents. The data analysis technique was conducted through content analysis, by examining various philosophical concepts and their application in the contemporary education system. The results show that philosophical thinking contributes to shaping an adaptive curriculum, innovative learning methods, and the role of teachers as facilitators in the educational process. In addition, philosophy also plays a role in designing educational policies that are responsive to social and technological changes. By understanding the relevance of philosophy in education, it is hoped that the modern education system can produce individuals who are not only academically competent, but also have high moral, social and ethical awareness. Therefore, the integration of philosophical thinking in education needs to be continuously developed in order to create a learning system that is more holistic, innovative, and in accordance with the needs of the times.